Gobernanza territorial y conflictos de uso por la extracción de recursos marinos en áreas de pesca responsable: Caso Paquera – Tambor, Costa Rica - Calvo González, Isabel (2020)
The present work tries to expose the diverse conflicts for the use of the space and the marine resources in the Marine Area of ??Responsible Fishing of Paquera and Tambor, in the area of ??the Gulf of Nicoya in the Central Pacific of Costa Rica. This marine area is a marine spatial planning strategy that is managed as of 2014, as a proposal for territorial governance. To understand the dynamics of territorial governance and its relationship with social, economic and environmental development, one must first identify the various conflicts between the actors with some type of territorial registration; as well as the global dynamics of the market that support the construction of a concrete vision and action on the fishing resource and the competition for extraction spaces. Regarding territorial governance in the Paquera-Tambor marine responsible fishing area (AMPR), it should be pointed out that, despite being spaces where local actors play an important role, the institutions try to co-opt the processes. What this cooptation generates are conflicts that materialize in the struggle between fishermen for their fishing or conservation areas, the institutional capacity not having the resolution or minimization of the conflict.